Counseling on the Utilization of Tourism Linguistic Landscape Theory at the Museum Subang West Java - Roni Nugraha Syafroni (UKInstitute, 2023)
Linguistics has developed as a scientific discipline that can be side by side with disciplines outside of language. One of them is with the discipline of landscape and tourism science. In this article, Servant analyzes labeling within the Museum Subang by utilizing the theory of tourism linguistic landscape. Within the Museum Subang area, labeling is spread from the entrance gate to the back of the museum building. There are seven labels that Servicemen take by documenting using a digital camera. Then, the Servant conducts counseling on the results of the analysis of the seven labels that the Servant received earlier, to officers or guides who are in the museum area. The purpose of this service is to introduce the theory of tourism linguistic landscapes to the public, in this case officers or guides. The methods of implementing community service activities used in this community service are direct approaches, surveys, counseling, discussions, documentation, and literature. The results and conclusions of this dedication are that linguistics can be useful to be juxtaposed with other sciences and is beneficial for the wider community's knowledge in a comprehensive manner.